2017 IEEE International Symposium on Information Theory (ISIT) 2017
DOI: 10.1109/isit.2017.8006900
|View full text |Cite
|
Sign up to set email alerts
|

Minimax optimal estimators for additive scalar functionals of discrete distributions

Abstract: In this paper, we consider estimators for an additive functional of φ, which is defined as θ(P ; φ) = k i=1 φ(pi), from n i.i.d. random samples drawn from a discrete distribution P = (p1, ..., p k ) with alphabet size k. We propose a minimax optimal estimator for the estimation problem of the additive functional. We reveal that the minimax optimal rate is characterized by the divergence speed of the fourth derivative of φ if the divergence speed is high. As a result, we show there is no consistent estimator if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…, we have φ (1) (p) > 0 for p ∈ (0, p 1 ). From continuity of φ (1) , φ (1) (p) has the same sign in p ∈ (0, p 1 ]. Thus, if β + δ is small enough so that β + δ < p 1 ∧ 1 2 , we have…”
Section: Appendixmentioning
confidence: 99%
See 4 more Smart Citations
“…, we have φ (1) (p) > 0 for p ∈ (0, p 1 ). From continuity of φ (1) , φ (1) (p) has the same sign in p ∈ (0, p 1 ]. Thus, if β + δ is small enough so that β + δ < p 1 ∧ 1 2 , we have…”
Section: Appendixmentioning
confidence: 99%
“…The first term is improved from Eq. (1). It indicates that the introduced estimator can consistently estimate Shannon entropy even when k n, as long as n k/ ln k. While the recent efforts revealed the minimax optimal estimators for the additive functionals with some specific φ, there is no unified methodology to derive the minimax optimal estimator for the additive functional with general φ. Jiao et al [11] suggested that their proposed estimator can be extended for general additive functional θ.…”
Section: A Related Workmentioning
confidence: 99%
See 3 more Smart Citations